2022
DOI: 10.1126/scitranslmed.abo3605
|View full text |Cite
|
Sign up to set email alerts
|

Combination cancer immunotherapies: Emerging treatment strategies adapted to the tumor microenvironment

Abstract: Immune checkpoint blockade (ICB) has revolutionized cancer treatment. However, resistance to ICB occurs frequently due to tumor-intrinsic alterations or extrinsic factors in the tumor microenvironment. This Viewpoint aims to give an update on recent developments in immunotherapy for solid tumors and highlights progress in translational research and clinical practice.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

3
48
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 100 publications
(62 citation statements)
references
References 74 publications
3
48
0
Order By: Relevance
“…Furthermore, inhibition or resistance to ferroptosis in vivo emaciates the synergy between immunotherapy and radiation therapy ( 99 ). Major immunosuppressive mechanisms in the tumor microenvironment include high PD-L1 expression and regulatory T cell infiltration ( 100 , 101 ). Radiation can target PD-L1-expressing cells and regulatory T cells ( 102 , 103 ).…”
Section: Ferroptosis In Antitumor Immunitymentioning
confidence: 99%
“…Furthermore, inhibition or resistance to ferroptosis in vivo emaciates the synergy between immunotherapy and radiation therapy ( 99 ). Major immunosuppressive mechanisms in the tumor microenvironment include high PD-L1 expression and regulatory T cell infiltration ( 100 , 101 ). Radiation can target PD-L1-expressing cells and regulatory T cells ( 102 , 103 ).…”
Section: Ferroptosis In Antitumor Immunitymentioning
confidence: 99%
“…Recent advancements in cancer immunology have shifted the paradigm of cancer treatment and has become one of the most prominent therapeutics for human cancers. This breakthrough has prolonged the survival of patients with relapsed or refractory metastatic cancers; however, only a subset of patients display favorable responses and most patients with immunologically cold solid tumors do not respond [ 46 , 47 ]. Emerging evidence has demonstrated that productive antitumor immune response is regulated in multiple cell types of TME and at an extraordinary level of orchestration of an array of coordinated biological processes, such as epigenetic modifications and metabolic reprograming.…”
Section: Arid1a-deficiency: An Immune-metabolic Vulnerabilitymentioning
confidence: 99%
“…Despite the overall impressive clinical effects of ICB in cancer treatment, not all patients respond to immunotherapy. Therefore, there is a substantial and unmet medical need for the development of biomarkers that could predict the response of individual patients to immunotherapeutic agents [ 46 , 47 ]. Recent findings that ARID1A deficiency is related to sensitivity to ICB therapy in multiple cancer types have paved the way of harnessing ARID1A as a novel target for cancer immunotherapy [ 11 , 62 , 63 , 64 , 65 , 66 , 67 , 68 , 69 , 70 , 71 , 72 ].…”
Section: Arid1a-deficiency: An Immune-metabolic Vulnerabilitymentioning
confidence: 99%
“…In addition, TME is critically involved in clinical intervention and changes treatment outcomes. Modulation of TME is useful for fine-tuning of therapy strategies (9)(10)(11).…”
Section: Introductionmentioning
confidence: 99%